Characteristics of brain function connection during different dxercise cycles of BaFa WuBu of Tai Chi - Shen, Qi-Qi; Yin, Heng-chan; Cui, Lei; Hou, Jin-Mei; Xia , Tong (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details